Influence of the melanin-glucan complex on the radiosensitivity of cells of patients with premalignant pathology of breast - Domina, E.A.; Smolanka, I.I.; Mikhailenko, V.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
The authors present their own results of studying the influence of the melanin-glucan complex (MGC) on the radiosensitivity of blood lymphocytes in patients with premalignant pathology of breast, depending on the drug concentration. A test system of peripheral blood lymphocytes was used with a metaphase analysis of chromosome aberrations (24 observations). It is observed that MGC affects the radiosensitivity of blood cells in patients by reducing the level of induced aberrations of chromosomes, including radial markers. The most effective radioprotective effect of MGC appears at a concentration of the drug of 2.0 μg/ml blood. Given its antioxidant properties, these findings confirm the essential role of the oxidative status of cells in the formation of their chromosomal instability.